Muhasabah Approach In Assessing Students' Social Behaviour In Madrasahs As A Solution In Overcoming Moral Degradation - Raikhan (Program Studi Pendidikan Agama Islam (PAI), 2024)
The degradation of moral values among students in Indonesia has become increasingly evident over the last decade, prompting the development of character education programs, including the Pancasila student profile strengthening program. This study examines the use of the muhasabah approach (self-reflection) as a tool for assessing students' social behavior in madrasahs. Through interviews, observations, and data analysis, the study reveals that using muhasabah in assessments—focusing on principles of contextuality, fairness, openness, and communicative practices—significantly improves students' morality. Key indicators such as discipline, responsibility, honesty, and enthusiasm are evaluated using observation tools, attendance records, and recognition systems. The findings suggest that muhasabah not only fosters moral improvement but also reduces radicalism among students. The study underscores the potential of social assessments in educational institutions to instill strong moral values and contribute positively to national character development